2018
DOI: 10.1155/2018/9845123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Seven Clinical Tumor Markers in Diagnosis of Non-Small-Cell Lung Cancer

Abstract: Background The correlation between tumor markers (TM) and TNM stage of non-small-cell lung cancer (NSCLC) has not been widely reported. Methods TM levels (CEA, CA125, CA15-3, CA19-9, CA72-4, CYFRA21-1, and SCC-Ag) in 424 cases of lung adenocarcinoma (LAC), 166 cases of lung squamous cell carcinoma (LSCC), and 103 cases of benign chest disease (BCD) were analyzed before treatment. Results By Kendall's tau-b correlation analysis, CEA, CA125, CA15-3, CA19-9, CA72-4, CYFRA21-1, and SCC-Ag were correlated with T st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 27 publications
2
52
1
2
Order By: Relevance
“…Exclude patients without tumor size data, only 335 cases of lung adenocarcinoma were studied in part 1. It was noteworthy that the conclusions were consistent with the previous 424 cases of lung adenocarcinoma . Tumor size largely determines T stage.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Exclude patients without tumor size data, only 335 cases of lung adenocarcinoma were studied in part 1. It was noteworthy that the conclusions were consistent with the previous 424 cases of lung adenocarcinoma . Tumor size largely determines T stage.…”
Section: Discussionsupporting
confidence: 88%
“…It was noteworthy that the conclusions were consistent with the previous 424 cases of lung adenocarcinoma. 13 Tumor size largely determines T stage. The correlations between TM levels and tumor size were consistent with the correlations between TM levels and T stage.…”
Section: Discussionmentioning
confidence: 99%
“…Because traditional TAA markers, such as cytokeratin 19 fragment antigen (CYFRA21-1), neuron-speci c enolase (NSE), carcinoembryonic antigen (CEA), and squamous cell carcinoma antigen (SCC), remain widely used as reference diagnostics for lung cancer, 37 we compared the 7-AAB panel with the combination of these traditional TAAs in the diagnosis of LC. We found that the 7-AAB panel was good in the early stages of lung cancer, while the traditional tumor markers showed a higher sensitivity with latestage LC.…”
Section: Discussionmentioning
confidence: 99%
“…The serum CEA levels were higher in patients with colon cancer when compared to healthy individuals, and this led to its clinical application as a diagnostic biomarker for colorectal cancer (17). Recently, the serum levels of CEA and the trend of its changes in the treatment process have been previously validated (18). Thus, some patients with elevated CEA levels were easily misdiagnosed as lung cancer.…”
Section: Discussionmentioning
confidence: 99%